Brain MRI findings in non-ketotic hyperglycemic crisis: Case report - Laura Estefanía Arenas-Vargas; Ruben Darío Arenas-Diaz; Enrique Hernandez-Rojas; Fabián Riaño-Montañez (Case Reports)
Introduction: Seizures related to metabolic disorders are common phenomena in many clinical contexts. However, clinical manifestations and neuroimaging findings in the context of a hyperglycemic crisis are less frequent phenomena with unclear pathophysiology.